2020
DOI: 10.1038/s41477-020-00783-z
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of adoption of climate-resilient crops by small-scale producers in low- and middle-income countries

Abstract: Climate-resilient crops and crop varieties have been recommended as a way for farmers to cope with or adapt to climate change, but despite the apparent benefits, rates of adoption by smallholder farmers are highly variable. Here we present a scoping review, using PRISMA-P (Preferred Reporting Items for Systematic review and Meta-Analysis Protocols), examining the conditions that have led to the adoption of climate-resilient crops over the past 30 years in lower- and middle-income countries. The descriptive ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(105 citation statements)
references
References 42 publications
3
74
0
Order By: Relevance
“…In this, 3D-breeding is a promising approach that could add to conventional breeding increasing varietal performance in smallholder agriculture, which accounts for the largest share of the global farms 7 . In those settings, the adoption rate of current breeding innovation may be suboptimal due to socioeconomic and environmental factors 9,21,[31][32][33] . Climate change is pushing these farming systems to the edge of their adaptation capacity with increasing pressure from pest and diseases 34,35 , threats of yield loss 36,37 and increased seasonal climatic variability 38,39 , calling for tailored solutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this, 3D-breeding is a promising approach that could add to conventional breeding increasing varietal performance in smallholder agriculture, which accounts for the largest share of the global farms 7 . In those settings, the adoption rate of current breeding innovation may be suboptimal due to socioeconomic and environmental factors 9,21,[31][32][33] . Climate change is pushing these farming systems to the edge of their adaptation capacity with increasing pressure from pest and diseases 34,35 , threats of yield loss 36,37 and increased seasonal climatic variability 38,39 , calling for tailored solutions.…”
Section: Resultsmentioning
confidence: 99%
“…To respond to local cropping needs impacted by climate change, breeders need to find new ways to accelerate variety development while directly addressing G E M interactions to the fullest 3,8,9 . Mobilizing farmers' traditional knowledge of crop varieties and local adaptation can address this challenge and enhance adoption of improved varieties 6,[10][11][12] in a coherent, decentralized breeding program relying on farmer-participatory selection [13][14][15] .…”
mentioning
confidence: 99%
“…Differences in the quantitative attribution in rice production between NK and its neighbors (SK and China) reflected the importance of adaptation based on social resilience to mitigate the adverse effects of extreme climate. Food security may benefit most from the changes in adaptive capacity under future climate change, such as in the fields of agricultural practices, economic development 35 , resource use, and social cognition 36 . Irrigation 37 , fertilization, conservation tillage 38 , and crop breeding are being given much attention, with more focus given to increasing yields.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the impact of climate change on maize genetic diversity can be substantial and needs to be further studied, especially in small-scale farms that depend on rainfall for maize cultivation [82]. Acevedo et al (2020, [83]) recently surveyed literature and identified major determinants for farmers' adoption of climate resilient varieties or crops, i.e., climate-change-related drivers for replacing previously preferred varieties or crops.…”
Section: Genetic Erosionmentioning
confidence: 99%